Effects of transcranial pulsed electromagnetic field stimulation on quality of life in Parkinson's disease. (17th April 2018) - Morberg, B. M.; Malling, A. S.; Jensen, B. R.; Gredal, O.; Bech, P.; Wermuth, L.
Abstract : Background and purpose: Pulsed electromagnetic fields induce a protective and anti‐inflammatory effect in the nervous system primarily due to growth factor upregulation that possibly abates neurodegeneration in Parkinson's disease (PD). This study investigated treatment effects of transcranial pulsed electromagnetic fields (T‐PEMFs) on quality of life in PD and the feasibility and safety of this treatment. Methods: In this double‐blinded clinical study, 97 participants with idiopathic PD (Hoehn & Yahr stage I–IV), on optimal medical anti‐parkinsonian treatment, were block randomized (3:3) to either active ( n = 49) or placebo treatment ( n = 48). Treatment with T‐PEMFs entailed one daily 30‐min home treatment for eight consecutive weeks. The 39‐item Parkinson's Disease Questionnaire (PDQ‐39) was assessed at baseline and endpoint. A special questionnaire was used to profile adverse events by interviewing the participants over the full treatment period. Treatment compliance was accounted for by daily treatment registration. Results: The active group improved with respect to clinical effect size for the two dimensions, i.e. mobility and activities of daily living, compared with the placebo group. No between‐group differences were found for the remaining PDQ‐39 dimensions. There were no between‐group difference in adverse events. Treatment compliance was 97.9%. Conclusion: Treatment with T‐PEMFs improved mobility and activities of daily living scores for clinical effect size only in the active group, indicating a positive treatment response for motor symptoms. No difference was found between the two groups for the remaining PDQ‐39 dimensions. The treatment had no or only mild adverse events and was performed with high compliance.